Systematics of Primary Education Content on the Base of Axiological Paradigm (Journal of Pedagogical Inventions and Practices, 2023)
This article examines the concept of national axiology and its integration into the primary education system in Uzbekistan. Through literature analysis and methodology, the research examines the main components of national axiology and its connection with the cultural identity of Uzbekistan. The results show that by effectively introducing national axiology into primary education, it is possible to create opportunities for cultural consciousness and selfawareness, and the formation of moral values in students